Use of Cloud Computing Applications in Reference Services - Tavluoğlu, Canan; Korkmaz, Ayse (Information World, 2014)
Cloud computing is a computing platform that allows access the information over internet by using desktop computers, laptops, tablet PCs and smart phones without any software and storage unit. Many organizations use this technology and save time and money, such as libraries. Libraries have been adopting their reference services to the new technology and library services have been moving to the cloud. This paper defines cloud computing, presents the opportunities and challenges, also include how to use cloud based applications in reference services. A survey was applied to identify the use of cloud based Software as a Service (SaaS) models by references librarians who work at university libraries in Ankara. According to results, the degree of usage of this tools generally low.